Prevalence and correlates of sex-selective abortions and missing girls in Nepal: evidence from the 2011 Population Census and 2016 Demographic and Health Survey - Channon, Melanie Dawn (BMJ Open, 2021)
OBJECTIVES: These were to: (1) produce national and subnational estimates of the sex ratio at birth (SRB) and number of missing girl births in Nepal and (2) understand the socioeconomic correlates of these phenomena. DESIGN: Observational secondary data analysis of (1) the 2011 population census of Nepal and (2) the Nepal Demographic and Health Survey (DHS) 2006, 2011 and 2016. SETTING: Nepal. PARTICIPANTS: (1) 2 567 963 children age 0–4 in the 2011 population census and (2) 27 329 births recorded in DHSs. PRIMARY AND SECONDARY OUTCOMES: We estimate the SRB, and number and proportion of missing girls in the year and 5 years before the census by district. We also calculate conditional sex ratios (the SRB dependant on parity and sex of previous children) by province, time, education and wealth. RESULTS: We find that 11 districts have significantly skewed sex ratios at birth in the 2011 population census, with the highest SRBs observed in Arghakhanchi (SRB=127) and Bhaktapur (SRB=123). 22 540 girl births were missing in the 5 years before the 2011 population census. Sex-selective abortion is geographically concentrated, especially in the Kathmandu Valley and Lumbini Province, with 53% of missing girls found in only 11 out of 75 districts. DHS data confirm this, with elevated conditional sex ratios observed in Bagmati and Lumbini Provinces; conditional sex ratios where previous births were all female also became more skewed over time. Skewed sex ratios are concentrated among wealthier more educated groups. CONCLUSIONS: It is clear that sex selection will persist and develop in Nepal unless a coordinated effort is made to address both the demand for and supply of this service. Policies should be holistic and encompass economic and legal gender equity, and strengthen monitoring mechanisms to prevent technology misuse, without jeopardising the right to safe, free and legal abortion.